Reliability analysis of truss structures considering complete failure paths and using the FLHB model - Felipe,Túlio Raunyr Cândido (2021)
abstract: The study of progressive collapse of structures using numerical models requires accurate modeling of geometrical nonlinearity and material failure behavior. Numerical models must demonstrate stability, such that localized member failures do not trigger numerical instabilities. Also, algorithms should be efficient, to limit the computational burden of analyzing multiple responses when considering the effects of uncertain loads, geometric and material variables. In this scientific domain, a comprehensive non-linear ductile-damage truss-element model has been recently presented by the authors. The model accounts for the geometrical and material nonlinearities observed during progressive collapse of structural systems. In this paper, the Felipe-Leonel-Haach-Beck (FLHB) model is calibrated to describe the response of Ultra-High-Performance Fiber Reinforced Concrete (UHPFRC). Based on a limited number of UHPFRC experimental curves, statistics of FLHB model parameters are obtained. These are employed in the probabilistic analysis of failure paths of truss structures under progressive collapse. Monte Carlo Simulation and the First Order Reliability Method are employed in the probabilistic failure path analyses. Six application examples demonstrate the accuracy, robustness, and efficiency of the FLHB model in evaluation of failure paths of realistic structural systems.